Graphene technology : from laboratory to fabrication - Nazarpour, Soroush; Waite, Stephen R. (Wiley-VCH, 2016)
Filling the gap between publications for industrial developers and academic researchers on graphene synthesis and its applications, this book presents the essential aspects for the successful upscaling of graphene production. After an introduction to graphene, its synthesis and characterization, the text covers a wide variety of graphene composites and compounds. The larger part of the book discusses various applications where graphene has been successfully integrated into technologies, including uses in the energy sector, oil and gas industry, biomedical areas, sensors and coatings. Finally, the book concludes with a summary and a look at the future of graphene technology, including a market review. With its focus on applications, this is equally useful for both academic and industrial users.